Education and Regional Languages in Indonesia: Between Necessity, Indifference and Regret - Jérôme Samuel (Moussons)
This article presents the language and, in particular, educational policies implemented in Indonesia since 1945 with regard to regional languages. The rise of the national language, Indonesian (Bahasa Indonesia), to undisputed status, now spoken and understood by almost the entire population, has gone hand in hand with a significant decline in the other indigenous languages of the archipelago, all of which have the status of regional languages. The prevailing attitude, both within educational structures and as expressed in normative texts, has been one of general indifference on the part of key stakeholders (educators, policymakers, politicians) toward regional languages. However, until the 1990s, this indifference, sometimes tinged with hostility, gradually shifted toward a more positive stance, marked by an increasing awareness of issues related to local identity, linguistic diversity, and the interests of children.